Fremtidslegender: Musikalsk fortid og nutid i David Bowies dystopier - Michelsen, Morten (Danish Yearbook of Musicology, 1999)
Future Legends – Musical Past and Future in the Dystopias of David Bowie In this article I argue that the music on the two David Bowie albums Diamond Dogs (RCA 1974) and Outside (BMG 1995) underlines and distinguishes the dystopias described in the lyrics. A discussion of science fiction in films (including the film scores) and of some of the associations created by the genres rock, disco, industrial, and drum’n’bass is used to establish the context on which Bowie and his audience probably draw in order to illuminate the lyrics musically. On Diamond Dogs the decadent future is illustrated by the use of contemporary (i.e. 1974) music associated with images of decadence (Rolling Stones, disco). An analysis of the “Sweet Thing” trilogy from this album shows that the dystopia is further distinguished by historical references to a bygone age with the musical as a model. This reference to musical theatre is supported by Bowie’s vocal performance in general, which can be characterized as the curious absence of the professional actor amidst his overwhelming presence. The same musical principles are followed on Outside, but the genres used there to illustrate decay are now the intensely noisy “industrial” and the computer-generated “drum’n’bass” genres. Parallels to the static harmony and the large spaces created in the production of the record can be found in the film scores for Blade Runner and 2001 – A Space Odyssey. The historical references stem from the acoustic piano playing Late Romantic and free-jazz clichés. I conclude that music can only function as a reference to the past and the present, not to the future. But by using absolutely contemporary music and mixing it with historical references, one can create the illusion of a music of the future, and it is with this device that Bowie has underlined and refined his two dystopian tales.